Efektifitas Pendidikan Kesehatan Terhadap Tekanan Darah Pada Lansia - Cory Nelia Damayanti; Mujib Hannan; Akhmad Feri Fatoni; Emdat Suprayitno (Fakultas Ilmu Kesehatan, 2019)
The incidence of hypertension especially faced by elderly demands the role of health workers to prevent and promote about healthy. Health education about hypertension for personal can give benefit habits, attitudes and knowledge related to the health of individuals, communities, and nations. Pre-experimental research design and One-Group Pretest-Posttest Design was used in this research. Population of this research were elderly with hypertension grade I blood pressure in Integrated Healthcare Center located in Pangarangan Village, Sumenep as many as 50 people. The samples of this research were 44 elderly suffered by hypertension. Purpossive sampling technique using inclusion and exclusion criteria approach. Data analysis in this study used the Paired samples t-test. The results of this study for elderly with blood pressure before given health education have basic pressure at stage II as many as 18 people (20.5%). Elderly’s blood pressure after given health education mostly at stage I as many as 37 people (42.1%) and effective health education against pressure blood pressure in elderly with hypertension in Integrated Healthcare Center Elderly in Pangarangan Village, Sumenep. Getting lower education level, getting high the risk of developing hypertension for elderly.